Electrophilic Cleavage of Nortricyclenes - Cappelli, Peter Frank (My University, 1975)
Mechanistic investigations pertaining to the electrophilic cleavages (acetic acid containing sulphuric acid) of the cyclopropyl group in 3-chloronortricyclene and 2-methyl-3-chloronortricyclene have been undertaken. For both compounds, the cyclopropyl bond which is furthest removed from halogen is preferentially cleaved. For 3-chloronortricyclene, studies using deuterated acid have established that for at least 70% of the products, the cyclopropyl carbon atom undergoing electrophilic attack experiences predominant retention of configuration (rentention: inversion > 14:1). Furthermore, almost exclusive inversion of configuration (inversion:retention ≈ was observed at the site of nucleophilic attack. Similarly, for cleavage of 2-methyl-3-chloronortricyclene in deuterated acid, rupture of the cyclopropyl bond furthest removed from halogen occurs with predominant retention of configuration at the site of electrophilic attach and accounts for most of the reaction pathway. Inversion of configuration at the carbon atom underogoing nucleophilic attack was observed.
These resutls suggest that fission of the cyclopropyl moiety in these systems occurs via initial edge protonation.
Syntheses of previously unknown 7-chloro-2-norbornyl brosylates-6-d listed below have been carried out. It is suggested that the spectrophotometrically determined γ-hydrogen deuterium isotope effects for ethanolyses of
(1) anti-7-chloro-exo-2-norbornyl brosylate-endo-6-d (1.11 ± 0.01),
(2) anti-7-chloro-exo-2-norbornyl brosylate-exo,exo-5,6-d2 (1.12 ± 0.01),
(3) syn-7-chloro-exo-2-norbornyl brosylate-endo-6-d (1.11 ± 0.01),
(4) syn-7-chloro-exo-2-norbornyl brosylate-exo,exo-5,6-d2 (1.11 ± 0.01) and
(5) anti-7-chloro-exo-2-norbornyl brosylate-endo-6-d (1.00 ± 0.01)
arise by homohyperconjugative interactions between the bonds at C-6 and the developing p orbital at C-2. These results are not consistent with the hypothesis that the γ-effects for solvolyses of exo-2-norbornyl brosylate-6-d arise by delocalization of the C-1 C-6 bond in the transition state.
From these studies, it was shown that during solvolyses of 7-chloro-exo-2-norbornyl brosylates-6-d, formation of 3-chloronortricyclene proceeded preferentially from a semi-U arrangement.
Keywords: Chemistry; Chemistry